The role of SGLT2 inhibitors in protecting cardiovascular health: beyond glycaemic control - Abed Alharbi, Samar; Alsubaiei, Amal Ahmad; Alkhalifah, Ali Hussain; Alshehri, Abdulrahman Abdulaziz; Alhaggas, Shoog Soliman; Alhuthli, Shahad Marwan; Alfaqih, Yousef Hassan; Alnajjar, Wed Ziyad; Alshaban, Ghaida Abdulla; Ahmed, Mahmood Sameer; Alqarni, Abdulkarem Sarhan (International Journal Of Community Medicine And Public Health, 2025)
Sodium-glucose cotransporter 2 (SGLT2) inhibitors, also known as Gliflozins, are a class of anti-diabetic medications initially developed for glycemic control in patients with type 2 diabetes mellitus (T2DM). T2DM patients are at a significantly higher risk of adverse outcomes, including heart failure, atherosclerotic cardiovascular disease, and renal diseases. Unlike traditional hypoglycemic agents, SGLT2 inhibitors have demonstrated notable cardiovascular benefits. Four SGLT2 inhibitors-Canagliflozin, Empagliflozin, Ertugliflozin, and Dapagliflozin—are currently approved by regulatory agencies such as the European Medicines Agency and the US Food and Drug Administration. Various mechanisms have been proposed to explain the cardioprotective effects of SGLT2 inhibitors, extending their therapeutic potential beyond glycemic control. The renal benefits of SGLT2 inhibitors contribute to cardiovascular outcomes, including reductions in albuminuria and slowing of chronic kidney disease progression. This review explores the impact of SGLT2 inhibitors on cardiovascular health in diabetic and non-diabetic populations, highlighting their ability to reduce renal and cardiovascular risks. Current evidence underscores their transformative role in managing T2DM and cardiovascular diseases. Furthermore, these findings pave the way for the development of innovative therapeutic strategies targeting diabetes and cardiovascular comorbidities. Additional research is needed to better understand the potential benefits of SGLT2 inhibitors in non-diabetic individuals.